2008
DOI: 10.1097/bsd.0b013e3181453dc6
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle Screw Placement With a Free Hand Technique in Thoracolumbar Spine: Is It Safe?

Abstract: Pedicle screw placement with a free hand technique after reviewing preoperative imaging seems to be accurate, reliable, and safe adjunct for the placement of thoracolumbar spine screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 38 publications
1
70
0
1
Order By: Relevance
“…Whereas, some surgeons believe that there is no need to use navigation system for pedicle screw placement in lumbar spine as lumbar pedicles are large enough to guarantee accuracy and safety. In addition, conclusions reported in different literature are not consistent [17][18][19]. Inconsistent conclusions, as well as varying experiences in different research centers, result in application of three-dimensional fluoroscopy-based navigation in lumbar spine being questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, some surgeons believe that there is no need to use navigation system for pedicle screw placement in lumbar spine as lumbar pedicles are large enough to guarantee accuracy and safety. In addition, conclusions reported in different literature are not consistent [17][18][19]. Inconsistent conclusions, as well as varying experiences in different research centers, result in application of three-dimensional fluoroscopy-based navigation in lumbar spine being questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Additional usage of fluoroscopy by Weinstein et al in another cadaveric study of pedicle screw insertion from T11-S1 decreased the overall pedicle "miss" rate to 21% [15]. Further additional usage of pedicle probing with a flexible ball-tipped probe decreased the medial and inferior wall violation to 2% [thirteen of 640 screws] in a study by Karapinar et al [16]. In an analysis of 3204 thoracic pedicle screws inserted with "free-hand" technique with adjuvant pedicle probing, fluoroscopy and neurophysiologic monitoring, only 1.7% incidence of asymptomatic medial wall violation was noted [4].…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies had different patient groups with alternative treatment options. [2][3][4][5][6][7][8]10,11,16,20,21,[24][25][26][29][30][31][32][33][34][35][36]38,43,44,47,48,51,52,54,55,57,58,[62][63][64][65] Thirteen studies were prospective, 25 were retrospective, and 1 study was both pro-and retrospective. 3 Seventeen studies reported a follow-up (mean follow-up 19.0 months, range 1-118 months).…”
Section: Resultsmentioning
confidence: 99%